2022
DOI: 10.1002/jad.12097
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal course of childhood bullying victimization and associations with self‐injurious thoughts and behaviors in children and young people: A systematic review of the literature

Abstract: Introduction: Bullying victimization has consistently been highlighted as a risk factor for self-injurious thoughts and behaviors (SITBs) in young people. This systematic review of prospective, community-based studies explored associations between bullying victimization (traditional/face-to-face and cyber) across the full spectrum of self-harm and suicidality, in children and young people aged up to (and including) 25 years. Importantly, associations by sex/gender were explored. Methods: MEDLINE, Embase, PsycI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 145 publications
1
6
0
Order By: Relevance
“…It was clear that the risk of bully (aRR = 1.89) varied, while gender was not identified as a risk for bullying victimization. Consistent with previous studies, rates of bully were higher in boys than in girls (Craig et al, 2009; Hosozawa et al, 2021; Wilson et al, 2022). These findings suggest that bullying other classmates may be a possible domination mechanism among boys and that they are willing to publicly report their aggression, so that their peers recognize their power.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It was clear that the risk of bully (aRR = 1.89) varied, while gender was not identified as a risk for bullying victimization. Consistent with previous studies, rates of bully were higher in boys than in girls (Craig et al, 2009; Hosozawa et al, 2021; Wilson et al, 2022). These findings suggest that bullying other classmates may be a possible domination mechanism among boys and that they are willing to publicly report their aggression, so that their peers recognize their power.…”
Section: Discussionsupporting
confidence: 91%
“…Multicenter studies conducted in about 40 countries have reported prevalence rates of about 13.0% for victimization and nearly 11.0% for school bully (Craig et al, 2009). At the same time, other studies have reported global variations in bully ranging from 10% to 65% (United Nations Educational, Scientific and Cultural Organization, 2017; Wilson et al, 2022). In our study, victimization of bullying was similar (9.3%).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations